Gut Microbiome Profiles in Colorectal Cancer Patients in Iraq - Fatima J. Kadhim; Zahid S. Aziz; Khalid S. Ibrahim (Microbiology Research)
Colorectal cancer (CRC) is the third most commonly diagnosed cancer globally, and is a significant contributor to both morbidity and mortality rates. Emerging research has promptly highlighted the potential role of the gut microbiome in the development and progression of CRC. This study aims to investigate the differences in gut microbiota between CRC patients and healthy individuals in Iraq, using 16S rRNA metagenomic sequencing on Illumina NovaSeq (PE250-Seq). A total of 21 stool samples were analyzed: 12 from early-stage CRC patients and nine from healthy controls. Bacterial DNA was extracted, followed by 16S rRNA amplicon sequencing to profile the microbial communities. The results indicated significant differences between the fecal microbiome of the two groups. Remarkably, CRC patients exhibited a marked reduction in Bacteroidota and an increase in Verrucomicrobiota compared to healthy controls. At the genus level, Prevotella, Faecalibacterium, Roseburia, Barnesiella, Eubacterium Lachnospiraceae_UCG_004, and Lachnospira were significantly less abundant in CRC patients compared to the healthy individuals, while Actinomyces, Monoglobus, Desulfovibrio, Akkermansia, and Bacteroides were highly enriched. In addition, diversity analyses further indicated decreased α-diversity and distinct β-diversity patterns in the CRC patients, suggesting significant shifts in the gut microbial composition. These findings underscore the potential of microbiome-based diagnostics and therapeutic strategies, with microbial alterations serving as biomarkers for CRC diagnosis. Further research needs to focus on elucidating the causal relationships and therapeutic potential of these microbiome changes in CRC management.